Balancing Specialist with Holistic Care: Challenges for Nurses in Managing Comorbidities of Hypertension and Diabetes in Orthopaedic Wards in Tanzania (Tanzania Medical Journal, 2025)
Background: The greater prominence of hypertension and diabetes in the Tanzanian population poses challenges for nursing care in hospital settings because of the increased likelihood of comorbidities among in-patients. Comorbidity refers to one or more conditions that exist during the clinical care of a patient who has a specific injury or disease as the presenting condition. This study looks at nursing care in orthopaedic in-patient wards where many patients also have high blood pressure and diabetes. Nurses spend more time with patients than other health workers and thus are better informed about patients’ overall health during hospital stays. Through interviews with nurses, this study explores how the hospital’s focus on orthopaedic care impacts on the nursing care also needed to manage hypertension and diabetes among patients in the wards.Objective: To investigate nurses’ experiences in balancing orthopaedic care of hospitalised patients with also caring for those patients with diabetes and hypertension and to enlist their suggestions and recommendations as professionals on how to adopt a more holistic approach to the care of these patients.   Methodology: A qualitative exploratory research design was used. In-depth interviews with ten registered nurses on orthopaedic wards explored their experiences of caring for orthopaedic in-patients with comorbidity conditions of hypertension or diabetes.  Purposive sampling was used to recruit nurses from male and female general wards. Based on in-depth reading of the English language transcripts, open coding of responses generated an initial set of codes. These were then grouped systematically into broader themes presenting evidence on the nature and sources of nursing challenges, implications for patients, and nurses’ proposals for improvement.Results: Key problems identified include: poor teamwork in the flow of information and communication between nurses and between nurses and other healthcare workers; deficiencies in the availability of functioning essential equipment and consumable and lack of training about comorbidities; and patients’ limited knowledge about their condition and medications. These challenges reinforce each other and amplify work pressure on nurses. This results in poorer health outcomes, delayed surgeries, prolonged wound healing, extended hospital stay, and increased mortality rates among patients with comorbidity.Conclusions and recommendations: This study concludes that moving from specialist towards more holistic care requires a systemic change at hospital level towards more effective team work and collaboration in information sharing between doctors, nurses and patients. This requires not only changes in the nursing process itself, but also in the overall approach to patient care.